Anne of Windy Poplars [Anna v Summerside anglicky] / book 4 - Montgomery, Lucy Maud, 1874-1942 (Anne of Green Gables - The complete collection, 2022)
Anne Shirley has left Redmond College behind to begin a new job and a new chapter of her life away from Green Gables. Now she faces a new challenge: the Pringles.